Clinical features of patients with MOG-IgG associated disorders and analysis of the relationship between fibrinogen-to-albumin ratio and the severity at disease onset - Li, Yue; Wang, Sai; Liu, Panpan; Ma, Jinxiu; Liu, Xinjing; Yuan, Jing (Frontiers in Neurology, 2023)
Objective: To investigate the differences in clinical features between minor and adult patients with first-episode MOG-IgG–Associated disorders (MOGAD) and to evaluate the relationship between the fibrinogen-to-albumin Ratio (FAR) level and the severity of neurological deficit at disease onset. Patients and methods: Our study retrospectively collected and analyzed the biochemical test results, imaging characteristics, clinical manifestation, Expanded Disability Status Scale score, and FAR. Spearman correlation analyses and logistic regression models were applied to identify the correlation between FAR and the severity of MOGAD. Receiver-operating characteristic curve analysis was applied to analyze the predictive ability of the FAR for the severity of neurological deficit. Results: Comparing the two groups based on age, fever (50.0%), headache (36.1%), and blurred vision (27.8%) were the most common clinical manifestations in the minor group (<18 years). However, in the adult group（≥18 years）, the most common symptoms were blurred vision (45.7%), paralysis (37.0%), and paresthesia (32.6%). Fever was more common in the minor group compared to the adult group. The most frequent clinical phenotype in the minor group was acute disseminated encephalomyelitis (ADEM) (41.7%), while optic neuritis (ON) (32.6%) was more common in the adult group. The difference in clinical phenotype between the two groups was statistically significant (P < 0.01). In both minor and adult patients, the most common lesions of cranial MRI were cortical/subcortical and brainstem, whereas, for the spine MRI, cervical and thoracic spinal cords were the most common. In binary logistic regression, the FAR was an independent risk factor for the severity of neurological deficit (OR =3.007; 95% CI =1.426-6.337; P=0.004). FAR (r=0.359, P=0.001) was positively correlated with the initial EDSS. The area under the ROC curve was 0.749. Conclusion: The current study found that there were age-dependent phenotypes in MOGAD, as ADEM was more commonly seen in patients aged<18 years, while ON was more frequently found in patients aged ≥18 years. A high level of the FAR was an independent indicator of more severe neurological deficit at disease onset in patients with a first episode of MOGAD.